Bernstein Collocation Method for Solving Nonlinear Fredholm-Volterra Integrodifferential Equations in the Most General Form - Ayşegül Akyüz-Daşcıoğlu; Neşe İşler Acar; Coşkun Güler (Journal of Applied Mathematics)
A collocation method based on the Bernstein polynomials defined on the interval [a,b] is developed for approximate solutions of the Fredholm-Volterra integrodifferential equation (FVIDE) in the most general form. This method is reduced to linear FVIDE via the collocation points and quasilinearization technique. Some numerical examples are also given to demonstrate the applicability, accuracy, and efficiency of the proposed method.